2003
DOI: 10.1063/1.1545099
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the degree of hydrogen bonding between quinoline and water by ultraviolet–visible absorbance spectroscopy in sub- and supercritical water

Abstract: Articles you may be interested inInsights into the ultraviolet spectrum of liquid water from model calculations: The different roles of donor and acceptor hydrogen bonds in water pentamers J. Chem. Phys. 137, 184301 (2012); 10.1063/1.4764044 High-resolution ultraviolet spectroscopy of p -fluorostyrene-water: Evidence for a σ -type hydrogen-bonded dimer Structures of hydrogen-bonded clusters of benzyl alcohol with water investigated by infrared-ultraviolet double resonance spectroscopy in supersonic jet J. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…2b. Osada et al 34 also reported that the frequency of quinoline, whose molecular structure is similar to pyridazine, does not show any change with temperature (25 -300˚C) in gaseous argon. Thus, the spectral shifts of pyridazine can be attributed mainly to the effect of the polarity of the solvent and hydrogen bonding.…”
Section: Dependence Of Spectral Shift On Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…2b. Osada et al 34 also reported that the frequency of quinoline, whose molecular structure is similar to pyridazine, does not show any change with temperature (25 -300˚C) in gaseous argon. Thus, the spectral shifts of pyridazine can be attributed mainly to the effect of the polarity of the solvent and hydrogen bonding.…”
Section: Dependence Of Spectral Shift On Conditionsmentioning
confidence: 99%
“…These phenomena mean that the local density around pyridazine is higher than the bulk density in the supercritical region, as described above. It has been reported that for benzophenone, 33 quinoline, 34 4-nitroaniline, 35 and 4-nitroanisole 40 in supercritical water, the differences between the local density and the bulk density are related to the free volume and the compressibility of the solvent. Therefore, in the liquid state and in a very high-temperature (450˚C) supercritical state, in which the isothermal compressibility is close to zero, the local density should be almost the same as the bulk one.…”
Section: Estimation Of the Local Density Around Pyridazinementioning
confidence: 99%
See 3 more Smart Citations